Pelatihan Penggunaan Aplikasi Canva untuk Meningkatkan Kemampuan Siswa dalam Membuat Bahan Promosi Sekolah di SMAN 03 Kota Bengkulu - Meta Natasya Putri; Indah Setyani; Marsanda Putri Muharani; Aida Nurdiana; Resti Amalia Putri (Yayasan Darussalam Bengkulu, 2025)
In the modern world of education, especially in supporting school promotion, knowledge and skills in graphic design are important components. This article discusses students' efforts to improve their skills by using Canva as a digital design tool to create posters, flyers, and social media content that promotes the school. Students are encouraged to actively learn Canva's features and use them to create creative, informative, and engaging promotional materials. This is done through a project-based learning approach. The results of this activity use the Asset Based Community Development method which emphasizes the assets and potential possessed by students. The results of the study showed that students better understood the elements of visual design, were more proficient in using Canva, and were more confident in presenting their work. In addition, Canva has also proven effective in improving students' collaboration, innovation, and digital skills. This article suggests incorporating Canva into the information technology curriculum or extracurricular activities to support the development of students' soft skills and digital literacy. Thus, students' ability to use technology for visual communication can be expanded.